Does organizational ethical climate influence auditors in perceiving ethical problems and forming ethical judgments? / Maheran Zakaria, Hasnah Haron and Ishak Ismail - Zakaria, Maheran; Haron, Hasnah; Ismail, Ishak (Research Management Institute (RMI), 2009)
The increasing cases of unethical behavior among auditors have led the public to distrust the credibility of this profession. The public accused that most of auditors with unethical behaviors are due to their motivation by revenue generation. Ironically, in the pursuits of generating revenue, some of auditors are willing to go beyond acceptable ethical standards, resulting to increase the probability of unethical judgments. As such, this triggers expectation that audit firms to strictly govern their members’ behavior within the ethical manner. Hence, this paper attempts to examine the influence of organizational ethical climate on auditors’ perceived ethical problems and ethical judgments. A total of 940 questionnaires were sent to auditors throughout Malaysia. However, an approximate of 250 questionnaires was returned but only 224 were usable. By using path analysis, of AMOS 16.0, the study found that organizational ethical climate influences auditors in perceiving ethical problems, while perceived ethical problems does influence ethical judgments. Finally, perceived ethical problems were found to mediate the relationship between organizational ethical climate and ethical judgments. Hence, these findings will be useful to those in auditing industry in their effort to improve auditors’ ethical perceptions and ethical judgments.